Collaboration Between Government and Community in Overcoming Domestic Violence: A Theory Analysis of Collaboration with A Systemic Approach and Face to Face Dialogue - Rira Nuradhawati; Muhammad Aldi Rahmandika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This article examines the implementation of collaboration between the government and the community in addressing domestic violence (DV) in Indonesia through an integrated collaboration theory framework. By combining Ansell and Gash's collaborative governance theory, which emphasizes face-to-face dialogue, Parsons' structural functionalism theory, which examines social systems, and Pfeffer and Salancik's resource dependence theory, which analyzes resource dependency, this study analyzes the architecture, processes, and power dynamics in collaborative efforts to address domestic violence. Using a critical literature review method of policy documents, official reports, and recent scientific works, this study identifies that formal collaborations such as the Integrated Service Unit (UPT PPA) have not been able to create structural transformation due to systemic communication distortions and entrenched power asymmetries. The findings indicate that despite the formality of collaboration, the dialogue that occurs is still instrumental and has not reached a deliberative level capable of deconstructing patriarchal norms. The study's conclusion emphasizes that effective collaboration requires a systemic approach that integrates institutional reform, restructuring power relations, and the creation of a truly egalitarian dialogue space.